The Influence of Competence, Training, and Work Discipline on Employee Performance at the Secretariat of the Directorate General of Capture Fisheries - Tasya Fadillah; Ahmad Cik; Melati; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the influence of competence, job training and work discipline on the performance of Sekretariat Direktorat Jenderal Perikanan Tangkap employees. The analytical method uses in this study are descriptive analysis and inferential analysis. Data analysis of several tests are instrument testing, multiple linear regression analysis, model feasibility testing, hypothesis testing t test and using the Statistical Product and Service Solution (SPSS) version 26.0 program. The subject of this research is an employee at the Sekretariat Direktorat Jenderal Perikanan Tangkap with 71 employee respondents with the method of collecting data through questionnaires. The results of multiple linear regression analysis show that the variables of Competence, Training and Work Discipline have a positive and significant effect on employee performance, which is shown in the coefficients table in the regression equation model Y = 0.150 X1 + 0.420 X2 + 0.466 X3 + 4.157. The results of the model's feasibility test are shown with a significant value of 0.000 which is shown in the ANOVA table, which means that the model in this study is feasible to use based on the significant value obtained. The conclusion from the results of the hypothesis with a partial t-test obtained a significant value on the competence variable of 0.044, while the training and work discipline variables have a significant value of 0.000. It can be partially concluded that the three independent variables have a significant influence on the dependent variable.